دور المركز التجاري في تغيير الوجه الحضاري لمدينة البويرة - علام, عثمان; العمري, نزيهة (جامعة الوادي- University of Eloued, 2017)
Bouira city occupies a strategic position being mediating the province and is considered its capital .The possession of many touristic sites such as Djurjura mountain and Feathers forest gives it the character of tourism and makes of it a center of attraction to many pepole from all over the country . And after that was a small town, Bouira province has witnessed significant development in terms of urbanism, basal facilities ,educational, health and even services infrastructures; this is thanks to development programs assigned from the state and commandment authorities. Among the infrastructures that figure out Bouira is the commercial center UNO which is widely known .This latter has become a destination to citizens from Bouira province and even outside to shop and relax, due to its vastness and the presence of all life requirements that citizens may need and even entertainment places for children. Therefore, the commercial center has increased the region's importance which has led to the expension of residential construction and thus the various public facilities. As such, the authorities care about the urbanisation of the region on agricultural lands expended throughout the city.
The role of the commercial center in changing the cultural face of the city of Bouira
مقال
Keywords: Bouira city, uno, trade Center.